The evaluation of the efficacy and safety of non-invasive neurally adjusted ventilatory assist in combination with INtubation-SURfactant-Extubation technique for infants at 28 to 33 weeks of gestation with respiratory distress syndrome. (March 2019) - Miyahara, Jun; Sugiura, Hiroshi; Ohki, Shigeru
Objectives: The aim of this study is to evaluate the efficacy and safety of non-invasive neurally adjusted ventilatory assist used after INtubation-SURfactant-Extubation in preterm infants with respiratory distress syndrome. Methods: We conducted a prospective observational study that included 15 inborn preterm infants at 28 (0/7) to 33 (6/7) weeks of gestation with respiratory distress syndrome in the period from April 2017 to October 2018. After INtubation-SURfactant-Extubation, infants underwent non-invasive neurally adjusted ventilatory assist. INtubation-SURfactant-Extubation failure was defined as follows: fraction of inspired oxygen requirement >0.4, respiratory acidosis, and severe apnea within 5 days after surfactant administration. Results: Two of the 15 (13.3%) infants showed INtubation-SURfactant-Extubation failure and required mechanical ventilation. No infants experienced any major complications such as pneumothorax, patent ductus arteriosus ligation, severe intraventricular hemorrhage, periventricular leukomalacia, retinopathy of prematurity, or death. Conclusion: The rate of INtubation-SURfactant-Extubation failure when non-invasive neurally adjusted ventilatory assist was used after INtubation-SURfactant-Extubation for preterm infants with respiratory distress syndrome was 13.3%. Non-invasive neurally adjusted ventilatory assist can be safely performed without severe complications for preterm infants soon after birth.